Estimation of Shear Wave Speed in the Rhesus Macaques Uterine Cervix - Huang, Bin (IEEE Trans Ultrason Ferroelectr Freq Control, 2016)
Cervical softness is a critical parameter in pregnancy. Clinically, preterm birth is associated with premature cervical softening and post-dates birth is associated with delayed cervical softening. In practice, the assessment of softness is subjective, based on digital examination. Fortunately, objective, quantitative techniques to assess softness and other parameters associated with microstructural cervical change are emerging. One of these is shear wave speed (SWS) estimation. In principle, this allows objective characterization of stiffness because waves travel more slowly in softer tissue. We are studying SWS in humans and rhesus macaques, the latter in order to accelerate translation from bench to bedside. For the current study, we estimated SWS in ex vivo cervices of rhesus macaques, n=24 nulliparous (never given birth) and n=9 multiparous (delivered at least 1 baby). Misoprostol (a prostaglandin used to soften human cervices prior to gynecological procedures) was administered to 13 macaques prior to necropsy (nulliparous: 7, multiparous: 6). SWS measurements were made at predetermined locations from the distal to proximal end of the cervix on both the anterior and posterior cervix, with 5 repeat measures at each location. The intent was to explore macaque cervical microstructure, including biological and spatial variability, to elucidate the similarities and differences between the macaque and the human cervix in order to facilitate future in vivo studies. We found that SWS is dependent on location in the normal nonpregnant macaque cervix, as in the human cervix. Unlike the human cervix, we detected no difference between ripened and unripened rhesus macaque cervix samples, nor nulliparous versus multiparous samples, although we observed a trend toward stiffer tissue in nulliparous samples. We found rhesus macaque cervix to be much stiffer than human, which is important for technique refinement. These findings are useful for guiding study of cervical microstructure in both humans and macaques.